Twinned-domain-induced magnonic modes in epitaxial LSMO/STO films. (2nd June 2017) - Wahlström, Erik; Macià, Ferran; Boschker, Jos E; Monsen, Åsmund; Nordblad, Per; Mathieu, Roland; Kent, Andrew D; Tybell, Thomas
Abstract: The use of periodic magnetic structures to control the magneto-dynamic properties of materials—magnonics—is a rapidly developing field. In the last decade, a number of studies have shown that metallic films can be patterned or combined in patterns that give rise to well-defined magnetization modes, which are formed due to band folding or band gap effects. To explore and utilize these effects in a wide frequency range, it is necessary to pattern samples at the sub-micrometer scale. However, it is still a major challenge to produce low-loss magnonic structures with periodicities at such length scales. Here, we show that for a prototypical perovskite, La 0.7 Sr 0.3 MnO3, the twinned structural order can be used to induce a magnetic modulation with a period smaller than 100 nm, demonstrating a bottom-up approach for magnonic crystal growth.